Book Review: Adams, Vicanne, editor. 2016: Metrics: What Counts in Global Health. (April 2018) - Curtis, Sarah
Adams, Vicanne, editor. 2016: Metrics: What Counts in Global Health . Durham, NC/London, UK: Duke University Press. 265 pp. 24.95 (Paperback). ISBN: 9780822360971.